Urban-Rural Innovation of the ABCD-based Mangunharjo Mandiri Sejahtera (MAMISERA) Program by Pertamina AFT Ahmad Yani - Respati, Iklima Nur; Riyadi, Agus; Suprihatiningsih, Suprihatiningsih; Putra, Muhammad Rinaldy; Winastu, Hadna Trie (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
The MAMISERA program by PT Pertamina Patra Niaga AFT Ahmad Yani in Mangunharjo Village addresses environmental and economic issues using the Asset-Based Community Development (ABCD) approach. Since 2020, it has focused on fish farming, production units, savings and loans, and waste processing. The program enhances local assets, including natural and human resources. Economically, the Trengginas Jaya Abadi cooperative, managed by 14 members, boosts income through milkfish product management. Environmentally, it converts milkfish waste into organic fertilizer and fish feed, reducing waste by 150 kg/year. Mangrove planting improves the marine ecosystem, cutting CO2 emissions by 0.0057 tons/year, while LPG-fueled feed machines reduce emissions by 0.00468 tons/year. This program integrates urban-rural synergy for sustainable development.